2018
DOI: 10.1103/physreve.98.052304
|View full text |Cite
|
Sign up to set email alerts
|

Identifying exogenous and endogenous activity in social media

Abstract: The occurrence of new events in a system is typically driven by external causes and by previous events taking place inside the system. This is a general statement, applying to a range of situations including, more recently, to the activity of users in Online social networks (OSNs). Here we develop a method for extracting from a series of posting times the relative contributions of exogenous, e.g. news media, and endogenous, e.g. information cascade. The method is based on the fitting of a generalized linear mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Endogenous factors are defined as interactions within social media or social networks, while exogenous factors are external influences on a community, such as news, catastrophes, and social events, which typically happen externally to social media. Previous studies have suggested that these factors can affect the shape of peaks in popularity profiles such as in search queries on Google, viewing activity on YouTube [13], and the adoption of hashtags on Twitter [19,44]. We develop a predictive model incorporating topic trends as exogenous factors and a method for estimating these factors from observational social media data.…”
Section: User Modeling In Social Mediamentioning
confidence: 99%
“…Endogenous factors are defined as interactions within social media or social networks, while exogenous factors are external influences on a community, such as news, catastrophes, and social events, which typically happen externally to social media. Previous studies have suggested that these factors can affect the shape of peaks in popularity profiles such as in search queries on Google, viewing activity on YouTube [13], and the adoption of hashtags on Twitter [19,44]. We develop a predictive model incorporating topic trends as exogenous factors and a method for estimating these factors from observational social media data.…”
Section: User Modeling In Social Mediamentioning
confidence: 99%
“…Various point process models have been proposed for predicting the final number of re-shares [19,21] and their temporal pattern [10] on social media. Furthermore, these models have been applied to interpret the endogenous and exogenous shocks to the activity on YouTube [22] and Twitter [23]. To the best of our knowledge, the proposed model is the first model incorporating a two-stage process that is an essential characteristic of the spread of fake news.…”
Section: Related Workmentioning
confidence: 99%
“…The endogenous factors mainly refer to intrinsic self-excitation mechanisms, while the exogenous factors come from environmental changes or other events that take place independently of events that have occurred in a system. Typical instances could be found in seismic dynamics [1][2][3][4], tweets in social networks [5], neuronal firing [6,7], and so on. In this respect, financial markets are the most representative.…”
Section: Introductionmentioning
confidence: 99%